Learning Creative Arts via Instructional Television - Michael Olubunmi Odewumi; Ayotunde Atanda Falade; Adewale Olusegun Adeniran (University of Maribor Press, 2018)
Television is an audio-visual box initially meant for entertainment, but it has developed to become a potential tool for instructions globally. The objectives of this study were to: identify television programme watched by the students and the students' response to creative arts learning via instructional television. The research used a descriptive cross-sectional survey method, and purposive sampling was employed to sample 10 schools in Ibadan metropolis, Nigeria. During the study questionnaire was administered to 350 students. The research question was answered and hypotheses tested using ANCOVA, and the t-test. The study concluded that the students fell about positive the use of television for learning in creative arts and the students should be encouraged to watch educational and enlightening programmes on television.